Evaluating the impact of seismic surveying on American plaice (Hippoglossoides platessoides) movement using acoustic telemetry in an offshore marine environment - Benjamin G.C. King; Khanh Q. Nguyen; Michael Piersiak; Pablo Borys; Coady Fitzpatrick; Jacqueline M. Hanlon; Dylan O'Neill; Corey J. Morris (Marine Pollution Bulletin, 2026)

Spatial Replication Is Important for Developing Landscape Genetic Inferences for a Wetland Salamander - Bryce S. Wade; Todd W. Pierson; Benjamin M. Fitzpatrick; Evin T. Carter (Molecular Ecology, 2025)
Habitat fragmentation is a pressing threat to wildlife populations, and maintenance of gene flow between populations is an essential goal of conservation. Resistance surfaces have emerged as an important tool for modelling connectivity and developing management strategies to mitigate effects of habitat fragmentation. However, recent studies have noted inconsistencies in the factors most strongly associated with connectivity across different landscapes. Thus, replication of genetic‐based resistance surface optimisation across landscapes may be necessary for making robust conclusions about the influence of environmental variables. Accordingly, replication represents a substantive challenge and opportunity in the field of landscape genetics. In this study, we conducted replicated landscape genetic analyses across five landscapes in Tennessee and Kentucky for a threatened wetland amphibian, the four‐toed salamander ( Hemidactylium scutatum ). We tested multiple hypotheses of how different landscape features that could directly affect small, desiccation‐intolerant amphibians (e.g., canopy cover) influenced gene flow and assessed the appropriate scale at which to model different features. We found some concordance in the landscape features that influenced gene flow (e.g., a common importance of forest cover and topography), but also some differences—potentially owing to the difference in variability of predictors across landscapes. We also found discordance in the scale of effect of different features across landscapes. Our work emphasises that flat areas of moist forest not bisected by roads may be important for H. scutatum conservation, and our replicated design allows us to identify relationships that would have been missed if only using one study site.

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

New evidence contradicts the rapid spread of invasive genes into a threatened native species - Benjamin M. Fitzpatrick; Evan McCartney-Melstad; Jarrett R. Johnson; H. Bradley Shaffer (Biological Invasions, 2024)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Genetic structure of restored Brook Trout populations in the Southern Appalachian Mountains indicates successful reintroductions - Rebecca J. Smith; David C. Kazyak; Matt A. Kulp; Barbara A. Lubinski; Benjamin M. Fitzpatrick (Conservation Genetics, 2024)

The companion dog as a model for inflammaging: a cross-sectional pilot study - Sarah M. Schmid; Jessica M. Hoffman; Jena Prescott; Holley Ernst; Daniel E. L. Promislow; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; et al. (GeroScience, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Banking on a new understanding: translational opportunities from veterinary biobanks - D. LaLonde-Paul; L. Mouttham; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; Virginia R. Fajt; Annette L. Fitzpatrick; Unity Jeffery; et al. (GeroScience, 2023)

Once-daily feeding is associated with better health in companion dogs: results from the Dog Aging Project - Emily E. Bray; Zihan Zheng; M. Katherine Tolbert; Brianah M. McCoy; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; et al. (GeroScience, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Amphibious mudskipper populations are genetically connected along coastlines, but differentiated across water - Joel B. Corush; Todd W. Pierson; Jen‐Chieh Shiao; Yukitoshi Katayama; Jie Zhang; Benjamin M. Fitzpatrick (Journal of Biogeography, 2022)
Aim Specialized life histories can restrict the way that organisms move through the landscape. Some fishes, such as mudskippers in the family Gobiidae, are obligately amphibious and require a terrestrial phase in which adults build burrows and lay eggs in mudflats. To evaluate whether this restricted, out‐of‐water phase might influence population structure in one such mudskipper, we tested whether populations separated by water are more differentiated than those connected along a coastline. Location South and East China Seas. Taxon Periophthalmus modestus (family: Gobiidae, subfamily: Oxudercinae) (Cantor 1842). Methods We collected 236 individuals from 10 locations around the East and South China Seas. We used a targeted capture sequencing method, RADcap, to call SNPs from 365 loci. We used multiple spatial and population genetics analyses and coalescent models to address the contemporary and historic biogeography of the species. Results The observed levels of genetic variation and population structure show populations of P. modestus are connected across large distances of continuous coastline and small spans of water. Restricted long‐distance dispersal across deep water has resulted in fragmentation of populations. We recovered no signal of isolation by distance, but instead, found genetic differentiation associated with regional groupings separated by large expanses of water. Main conclusions A limited dispersal phase significantly affects population structure in this amphibious fish. The restrictive amphibious life history may be a key factor in the present‐day distribution and population structure of P. modestus . Interactions between organismal life history and geography are critical for explaining the population genetic structure of a species.

Genetic data reveal fine-scale ecological segregation between larval plethodontid salamanders in replicate contact zones - Todd W. Pierson; Benjamin M. Fitzpatrick; Carlos D. Camp (Evolutionary Ecology, 2021)

Effects of the cannabinoid receptor agonist CP-55,940 on incentive salience attribution - Ali Gheidi; Lora M. Cope; Christopher J. Fitzpatrick; Benjamin N. Froehlich; Rachel Atkinson; Coltrane K. Groves; Clair N. Barcelo; Jonathan D. Morrow (Psychopharmacology, 2020)

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

A hierarchical Bayesian model to incorporate uncertainty into methods for diversity partitioning - Zachary H. Marion; James A. Fordyce; Benjamin M. Fitzpatrick (Ecology, 2018)
Recently there have been major theoretical advances in the quantification and partitioning of diversity within and among communities, regions, and ecosystems. However, applying those advances to real data remains a challenge. Ecologists often end up describing their samples rather than estimating the diversity components of an underlying study system, and existing approaches do not easily provide statistical frameworks for testing ecological questions. Here we offer one avenue to do all of the above using a hierarchical Bayesian approach. We estimate posterior distributions of the underlying “true” relative abundances of each species within each unit sampled. These posterior estimates of relative abundance can then be used with existing formulae to estimate and partition diversity. The result is a posterior distribution of diversity metrics describing our knowledge (or beliefs) about the study system. This approach intuitively leads to statistical inferences addressing biologically motivated hypotheses via Bayesian model comparison. Using simulations, we demonstrate that our approach does as well or better at approximating the “true” diversity of a community relative to naïve or ad‐hoc bias‐corrected estimates. Moreover, model comparison correctly distinguishes between alternative hypotheses about the distribution of diversity within and among samples. Finally, we use an empirical ecological dataset to illustrate how the approach can be used to address questions about the makeup and diversities of assemblages at local and regional scales.

Genome scale assessment of a species translocation program - Cassie M. Dresser; R. Michael Ogle; Benjamin M. Fitzpatrick (Conservation Genetics, 2017)

Pairwise beta diversity resolves an underappreciated source of confusion in calculating species turnover - Zachary H. Marion; James A. Fordyce; Benjamin M. Fitzpatrick (Ecology, 2017)
Beta diversity is an important metric in ecology quantifying differentiation or disparity in composition among communities, ecosystems, or phenotypes. To compare systems with different sizes ( N , number of units within a system), beta diversity is often converted to related indices such as turnover or local/regional differentiation. Here we use simulations to demonstrate that these naive measures of dissimilarity depend on sample size and design. We show that when N is the number of sampled units (e.g., quadrats) rather than the “true” number of communities in the system (if such exists), these differentiation measures are biased estimators. We propose using average pairwise dissimilarity as an intuitive solution. That is, instead of attempting to estimate an N ‐community measure, we advocate estimating the expected dissimilarity between any random pair of communities (or sampling units)—especially when the “true” N is unknown or undefined. Fortunately, measures of pairwise dissimilarity or overlap have been used in ecology for decades, and their properties are well known. Using the same simulations, we show that average pairwise metrics give consistent and unbiased estimates regardless of the number of survey units sampled. We advocate pairwise dissimilarity as a general standardization to ensure commensurability of different study systems.

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Monitoring and assessment of surface water acidification following rewetting of oxidised acid sulfate soils - Luke M. Mosley; Benjamin Zammit; Ann-Marie Jolley; Liz Barnett; Rob Fitzpatrick (Environmental Monitoring and Assessment, 2014)

Can genetic data confirm or refute historical records? The island invasion of the small Indian mongoose (Herpestes auropunctatus) - Arijana Barun; Matthew L. Niemiller; Benjamin M. Fitzpatrick; James A. Fordyce; Daniel Simberloff (Biological Invasions, 2013)

Doomed before they are described? The need for conservation assessments of cryptic species complexes using an amblyopsid cavefish (Amblyopsidae: Typhlichthys) as a case study - Matthew L. Niemiller; Gary O. Graening; Dante B. Fenolio; James C. Godwin; James R. Cooley; William D. Pearson; Benjamin M. Fitzpatrick; Thomas J. Near (Biodiversity and Conservation, 2013)

Transgressive Hybrids as Hopeful Monsters - Dylan R. Dittrich-Reed; Benjamin M. Fitzpatrick (Evolutionary Biology, 2013)

Tests of two methods for identifying founder effects in metapopulations reveal substantial type II error - R. Graham Reynolds; Benjamin M. Fitzpatrick (Genetica, 2013)

Lethal Effects of Water Quality on Threatened California Salamanders but Not on Co‐Occurring Hybrid Salamanders - MAUREEN E. RYAN; JARRETT R. JOHNSON; BENJAMIN M. FITZPATRICK; LINDA J. LOWENSTINE; ANGELA M. PICCO; H. BRADLEY SHAFFER (Conservation Biology, 2013)
Biological invasions and habitat alteration are often detrimental to native species, but their interactions are difficult to predict. Interbreeding between native and introduced species generates novel genotypes and phenotypes, and human land use alters habitat structure and chemistry. Both invasions and habitat alteration create new biological challenges and opportunities. In the intensively farmed Salinas Valley, California (U.S.A.), threatened California tiger salamanders ( Ambystoma californiense ) have been replaced by hybrids between California tiger salamander and introduced barred tiger salamanders ( Ambystoma tigrinum mavortium ). We conducted an enclosure experiment to examine the effects habitat modification and relative frequency of hybrid and native California tiger salamanders have on recruitment of salamanders and their prey, Pacific chorus frogs ( Pseudacris regilla ). We tested whether recruitment differed among genetic classes of tiger salamanders (hybrid or native) and pond hydroperiod (seasonal or perennial). Roughly 6 weeks into the experiment, 70% (of 378 total) of salamander larvae died in 4 out of 6 ponds. Native salamanders survived ( n = 12) in these ponds only if they had metamorphosed prior to the die‐offs. During die‐offs, all larvae of native salamanders died, whereas 56% of hybrid larvae died. We necropsied native and hybrid salamanders, tested water quality, and queried the California Department of Pesticide Regulation database to investigate possible causes of the die‐offs. Salamander die‐offs, changes in the abundance of other community members (invertebrates, algae, and cyanobacteria), shifts in salamander sex ratio, and patterns of pesticide application in adjacent fields suggest that pesticide use may have contributed to die‐offs. That all survivors were hybrids suggests that environmental stress may promote rapid displacement of native genotypes . Efectos Letales de la Calidad del Agua sobre Salamandras de California Amenazadas pero no sobre Salamandras Híbridas Concurrentes

Genetic analysis of an endemic archipelagic lizard reveals sympatric cryptic lineages and taxonomic discordance - R. Graham Reynolds; Matthew L. Niemiller; Benjamin M. Fitzpatrick (Conservation Genetics, 2012)

Hybridization between two gartersnake species (Thamnophis) of conservation concern: a threat or an important natural interaction? - John S. Placyk; Benjamin M. Fitzpatrick; Gary S. Casper; Randall L. Small; R. Graham Reynolds; Daniel W. A. Noble; Ronald J. Brooks; Gordon M. Burghardt (Conservation Genetics, 2012)

What can DNA tell us about biological invasions? - Benjamin M. Fitzpatrick; James A. Fordyce; Matthew L. Niemiller; R. Graham Reynolds (Biological Invasions, 2012)

Gene trees, species and species trees in the Ctenosaura palearis clade - Stesha A. Pasachnik; Arthur C. Echternacht; Benjamin M. Fitzpatrick (Conservation Genetics, 2010)

Corrigendum - MATTHEW L. NIEMILLER; PATRIK NOSIL; BENJAMIN M. FITZPATRICK (Molecular Ecology, 2010)

Geography disentangles introgression from ancestral polymorphism in Lake Malawi cichlids - MERYL C. MIMS; C. DARRIN HULSEY; BENJAMIN M. FITZPATRICK; J. TODD STREELMAN (Molecular Ecology, 2010)
Phenotypically diverse Lake Malawi cichlids exhibit similar genomes. The extensive sharing of genetic polymorphism among forms has both intrigued and frustrated biologists trying to understand the nature of diversity in this and other rapidly evolving systems. Shared polymorphism might result from hybridization and/or the retention of ancestrally polymorphic alleles. To examine these alternatives, we used new genomic tools to characterize genetic differentiation in widespread, geographically structured populations of Labeotropheus fuelleborni and Metriaclima zebra . These phenotypically distinct species share mitochondrial DNA (mtDNA) haplotypes and show greater mtDNA differentiation among localities than between species. However, Bayesian analysis of nuclear single nucleotide polymorphism (SNP) data revealed two distinct genetic clusters corresponding perfectly to morphologically diagnosed L. fuelleborni and M. zebra . This result is a function of the resolving power of the multi‐locus dataset, not a conflict between nuclear and mitochondrial partitions. Locus‐by‐locus analysis showed that mtDNA differentiation between species ( F CT ) was nearly identical to the median single‐locus SNP F CT . Finally, we asked whether there is evidence for gene flow at sites of co‐occurrence. We used simulations to generate a null distribution for the level of differentiation between co‐occurring populations of L. fuelleborni and M. zebra expected if there was no hybridization. The null hypothesis was rejected for the SNP data; populations that co‐occur at rock reef sites were slightly more similar than expected by chance, suggesting recent gene flow. The coupling of numerous independent markers with extensive geographic sampling and simulations utilized here provides a framework for assessing the prevalence of gene flow in recently diverged species.

Gene flow between an endangered endemic iguana, and its wide spread relative, on the island of Utila, Honduras: when is hybridization a threat? - Stesha A. Pasachnik; Benjamin M. Fitzpatrick; Thomas J. Near; Arthur C. Echternacht (Conservation Genetics, 2009)

Power and sample size for nested analysis of molecular variance - BENJAMIN M. FITZPATRICK (Molecular Ecology, 2009)
Analysis of molecular variance ( amova ) is a widely used tool for quantifying the contribution of various levels of population structure to patterns of genetic variation. Implementations of amova use permutation tests to evaluate null hypotheses of no population structure within groups and between groups. With few populations per group, between‐group structure might be impossible to detect because only a few permutations of the sampled populations are possible. In fact, with fewer than six total populations, permutation tests will never result in P ‐values r script that can be used to evaluate the minimum P ‐value for any sampling scheme. While it might seem counterintuitive that a large sample of individuals is uninformative about hierarchical structure, the power to detect between‐group differences depends on the number of populations per group and investigators should sample appropriately.

Distinctiveness in the face of gene flow: hybridization between specialist and generalist gartersnakes - BENJAMIN M. FITZPATRICK; JOHN S. PLACYK, JR; MATTHEW L. NIEMILLER; GARY S. CASPER; GORDON M. BURGHARDT (Molecular Ecology, 2008)
Patterns of divergence and polymorphism across hybrid zones can provide important clues as to their origin and maintenance. Unimodal hybrid zones or hybrid swarms are composed predominantly of recombinant individuals whose genomes are patchworks of alleles derived from each parental lineage. In contrast, bimodal hybrid zones contain few identifiable hybrids; most individuals fall within distinct genetic clusters. Distinguishing between hybrid swarms and bimodal hybrid zones can be important for taxonomic and conservation decisions regarding the status and value of hybrid populations. In addition, the causes of bimodality are important in understanding the generation and maintenance of biological diversity. For example, are distinct clusters mostly reproductively isolated and co‐adapted gene complexes, or can distinctiveness be maintained by a few ‘genomic islands’ despite rampant gene flow across much of the genome? Here we focus on three patterns of distinctiveness in the face of gene flow between gartersnake taxa in the Great Lakes region of North America. Bimodality, the persistence of distinct clusters of genotypes, requires strong barriers to gene flow and supports recognition of distinct specialist ( Thamnophis butleri ) and generalist ( Thamnophis radix ) taxa. Concordance of DNA‐based clusters with morphometrics supports the hypothesis that trophic morphology is a key component of divergence. Finally, disparity in the level of differentiation across molecular markers (amplified fragment length polymorphisms) indicates that distinctiveness is maintained by strong selection on a few traits despite high gene flow currently or in the recent past.

Recent divergence with gene flow in Tennessee cave salamanders (Plethodontidae: Gyrinophilus ) inferred from gene genealogies - MATTHEW L. NIEMILLER; BENJAMIN M. FITZPATRICK; BRIAN T. MILLER (Molecular Ecology, 2008)
Cave organisms occupy a special place in evolutionary biology because convergent morphologies of many species demonstrate repeatability in evolution even as they obscure phylogenetic relationships. The origin of specialized cave‐dwelling species also raises the issue of the relative importance of isolation vs. natural selection in speciation. Two alternative hypotheses describe the origin of subterranean species. The ‘climate‐relict’ model proposes allopatric speciation after populations of cold‐adapted species become stranded in caves due to climate change. The ‘adaptive‐shift’ model proposes parapatric speciation driven by divergent selection between subterranean and surface habitats. Our study of the Tennessee cave salamander complex shows that the three nominal forms ( Gyrinophilus palleucus palleucus , G. p. necturoides , and G. gulolineatus ) arose recently and are genealogically nested within the epigean (surface‐dwelling) species, G. porphyriticus . Short branch lengths and discordant gene trees were consistent with a complex history involving gene flow between diverging forms. Results of coalescent‐based analysis of the distribution of haplotypes among groups reject the allopatric speciation model and support continuous or recurrent genetic exchange during divergence. These results strongly favour the hypothesis that Tennessee cave salamanders originated from spring salamanders via divergence with gene flow.